Service Co-evolution in the Internet of Things - Tran, Huu Tam; Baraki, Harun; Geihs, Kurt (EAI Endorsed Transactions on Cloud Systems, 2015)
The envisioned Internet of Things (IoT) foresees a future Internet incorporating smart physical objects that offer hosted functionality as IoT services. This service-based integration of IoT will be smarter, easier to communicate with and more valuable for enriching our environment. However, the interfaces and services can be modified due to updates and amendments. Such modifications require adaptations in all participating parties. Therefore, the aim of this research is to present a vision of service co-evolution in IoT. Moreover, we propose a novel agent architecture which supports the evolution by controlling service versions, updating local service instances and enabling the collaboration of agents. In this way, the service co-evolution can make systems more adaptive, efficient and reduce costs to manage maintenance.
Keywords: Service co-evolution; Coordinating agents; IoT services; Web services; Adaptive services